Does the role of education in HIV prevention differ by the epidemic stage?: Evidence from 14 African countries - Ueyama, Mika (International Food Policy Research Institute, 2008)
A number of studies, in particular, epidemiological studies, have examined the association between socioeconomic characteristics and HIV infection, but the empirical evidence is mixed. Some studies found a positive correlation of HIV infection with socioeconomic status, but others found negative or insignificant relationship. Most existing studies did not explicitly pay attention to the fact that each study came from different countries (areas) at different stages of the epidemic. Because of data constraint, most studies examined ?snapshots? of factors associated with HIV infection in a specific country during a specific time frame (e.g., Malawi 2000) using cross-sectional data. Very few studies focus on how infection factors change with the depth of the AIDS epidemic. In other words, previous studies have just made an attempt to ?generalize? the relationship between education and HIV infection, assuming that the epidemic stage does not play a significant role.